Naẓariyyātu Dukhūli al-Islām ilā Āndūnīsiyā wa Āṡāruhā ‘alā al-Ittijāhāti li-Ḥarakāti al-Jam‘iyyāti al-Islāmiyyah: Nahḍatu al-‘Ulamā’ Namūẓajan - Rahman, Khildan Aulia (Faculty of Islam Nusantara, Nahdlatul Ulama University of Indonesia (Unusia) Jakarta., 2025)
The arrival of Islam in the archipelago or Nusantara is considered one of the most important events in the history of Indonesia. Numerous theories about Islamic arrival in the archipelago, along with the historical facts, are often seen as merely facts without purpose or practical relevance. However, for history buffs, this event is a crucial milestone that influenced the formation of society and the establishment of the state. Therefore, socio-historical studies are needed to understand the dynamics of the event, including examining the role of Nahdlatul Ulama (NU) as one of the significant socio-religious movements. Nahdlatul Ulama is the largest Islamic community organization in Indonesia that holds a rich heritage of Islamic culture. Along with the development of the archipelago towards the formation of the Unitary State of the Republic of Indonesia (NKRI), various Islamic and nationalism-based movements emerged with diverse thought and historical views, including theories about the arrival of Islam in the archipelago. A literature review of the direction of the NU movement provides a unique perspective in understanding these dynamics. This paper presents a comparative analysis of evolving theories on the arrival of Islam into the archipelago, and explores the attitudes of intellectuals affiliated with various movements, particularly within the framework of Nahdlatul Ulama's view as an axis of intellectual and historical upheaval.